2013
DOI: 10.1155/2013/154674
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal Trastuzumab Treatment of the Neoplastic Meningitis due to Breast Cancer: A Case Report and Review of the Literature

Abstract: We report the case of a 65-year-old woman, diagnosed with a breast cancer human epidermal growth factor receptor (HER2) previously negative, who developed leptomeningeal carcinomatosis and was treated with intrathecal (IT) trastuzumab (TST). After five doses of IT trastuzumab, at escalading doses, once weekly, the patient's neurological status stabilised, and that result was maintained for two months. There is evidence in the literature that breast cancer receptor status may change over time, and when it occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
(20 reference statements)
1
9
0
Order By: Relevance
“…Human epidermal growth factor receptor 2 (HER2) is overexpressed in approximately 30% of primary breast cancers and is associated with an increased risk of CNS involvement . Multiple reports describe response to IT trastuzumab, a humanized monoclonal antibody against HER2, in LM from HER2‐positive breast cancer . Preliminary results from a phase 1 trial of IT trastuzumab in patients with HER2‐positive breast cancer and LM demonstrated that it was well tolerated, and several phase 2 trials are ongoing (http://clinicaltrials.gov identifiers NCT01325207 and NCT01373710) .…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Human epidermal growth factor receptor 2 (HER2) is overexpressed in approximately 30% of primary breast cancers and is associated with an increased risk of CNS involvement . Multiple reports describe response to IT trastuzumab, a humanized monoclonal antibody against HER2, in LM from HER2‐positive breast cancer . Preliminary results from a phase 1 trial of IT trastuzumab in patients with HER2‐positive breast cancer and LM demonstrated that it was well tolerated, and several phase 2 trials are ongoing (http://clinicaltrials.gov identifiers NCT01325207 and NCT01373710) .…”
Section: Treatmentmentioning
confidence: 99%
“…83 Multiple reports describe response to IT trastuzumab, a humanized monoclonal antibody against HER2, in LM from HER2-positive breast cancer. [84][85][86][87][88][89] Preliminary results from a phase 1 trial of IT trastuzumab in patients with HER2-positive breast cancer and LM demonstrated that it was well tolerated, and several phase 2 trials are ongoing (clinicaltrials.gov identifiers NCT01325207 and NCT01373710). 90 Combination approaches are also being studied, with a phase 1 trial of lapatinib, a small-molecule dual tyrosine kinase inhibitor (TKI) that targets HER2 and EGFR, in combination with capecitabine, an antimetabolite chemotherapeutic, currently underway in HER2-positive patients with LM (clinicaltrials.gov identifier NCT02650752).…”
Section: Breast Cancermentioning
confidence: 99%
“…Trastuzumab has been successfully used systemically in HER-2 positive breast cancer. There are no studies for the intrathecal administration of trastuzumab, but several case reports and one review which showed a response after intrathecal injection of trastuzumab [96,97].…”
Section: Thiotepamentioning
confidence: 99%
“…In patients who develop leptomeningeal metastasis (involvement of pia and arachnoid matter), the usual intravenous dose does not help because of poor cerebrospinal penetration. In such cases, intrathecal trastuzumab is advocated along with systemic trastuzumab [ 17 ]. The dosing and the duration is controversial.…”
Section: Introductionmentioning
confidence: 99%